2009
DOI: 10.1007/s11661-009-9867-4
|View full text |Cite
|
Sign up to set email alerts
|

Impression Creep Characteristics of a Cast Mg Alloy

Abstract: The creep behavior of the cast Mg-6Al-0.3Mn alloy (AM60) was investigated by impression testing under constant punching stress in the range 150 to 650 MPa and at temperatures in the range 423 to 523 K, corresponding to 0.458 < T/T m < 0.567. The creep behavior can be divided into two stress regimes, with a change from the low-stress regime to the high-stress regime occurring, depending on the testing temperature, around 0.021 < (r/G) < 0.033. Based on the steady-state power-law creep relationship, the stress e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 39 publications
2
27
2
Order By: Relevance
“…The equivalent uniaxial creep strain rate (e ) and stress (r) can be evaluated from the impression velocity and impression stress, using the following two semiempirical relations: [31] r ¼ 4F…”
Section: A Creep Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent uniaxial creep strain rate (e ) and stress (r) can be evaluated from the impression velocity and impression stress, using the following two semiempirical relations: [31] r ¼ 4F…”
Section: A Creep Mechanismmentioning
confidence: 99%
“…[35] Stress exponents higher than 6 have also been assigned to a power-law breakdown regime, characterized by an activation energy higher than that of the selfdiffusion energy. [29,31] For instance, values as large as 195 kJ/mol have been reported for the creep activation energy of Mg-Al-Ca alloy in the power-law breakdown regime. [29] The obtained activation energies in the present study are much lower than have been reported for the power-law breakdown regime.…”
Section: ½3mentioning
confidence: 99%
“…The localized creep behavior of magnesium alloys has mostly been investigated by indentation tests using spherical indenters [20][21][22] and, in some more recent cases, by impression techniques. [23][24][25][26][27] The impression creep of Zr-containing Mg alloys has not been studied before, and thus, the aim of this study is to investigate the creep properties of this alloy using the impression testing technique.…”
Section: Introductionmentioning
confidence: 99%
“…Although impression creep technique has frequently been used for investigating creep properties of materials, it has not been standardized so far. It has been reported in many investigation that there is a good correspondence with results of both impression creep technique and those obtained from uniaxial tensile creep test [17,18]. Many investigations have been carried out on the impression creep properties of magnesium alloys, but impression creep properties of aluminum alloys have not been yet reported in the literature.…”
Section: Introductionmentioning
confidence: 84%